2016
DOI: 10.1080/09602011.2016.1140657
|View full text |Cite
|
Sign up to set email alerts
|

Computerised cognitive training in acquired brain injury: A systematic review of outcomes using the International Classification of Functioning (ICF)

Abstract: Computerised cognitive training (CCT) is an increasingly popular intervention for people experiencing cognitive symptoms. This systematic review evaluated the evidence for CCT in adults with acquired brain injury (ABI), focusing on how outcome measures used reflect efficacy across components of the International Classification of Functioning, Disability and Health. Database searches were conducted of studies investigating CCT to treat cognitive symptoms in adult ABI. Scientific quality was rated using the PEDr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 130 publications
3
48
1
Order By: Relevance
“…While participants in the CCT group described some increase in goal attainment, performance did not improve beyond WC at any timepoint. These results do not support the generalization of training to real-word benefit; a finding consistent with recent commentary (6,8). Within the context of equivocal memory rehabilitation outcomes to date (10), this study meaningfully contributes to the extant body of literature through confirmation of real-world improvement following group intervention training the use of compensatory memory strategies and highlights the potential utility of MSG in clinical practice.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…While participants in the CCT group described some increase in goal attainment, performance did not improve beyond WC at any timepoint. These results do not support the generalization of training to real-word benefit; a finding consistent with recent commentary (6,8). Within the context of equivocal memory rehabilitation outcomes to date (10), this study meaningfully contributes to the extant body of literature through confirmation of real-world improvement following group intervention training the use of compensatory memory strategies and highlights the potential utility of MSG in clinical practice.…”
Section: Discussionsupporting
confidence: 39%
“…In addition, the format of delivery differs. CCT training tasks are generally completed individually, with associated well-recognized advantages of low cost, wide availability and potential for at personalized use at home (8). MSG intervention is facilitated by a trained clinician and is delivered face-to-face in a group format, due, in part, to increased recognition of the multifaceted nature of memory dysfunction and limited economic resources (9).…”
mentioning
confidence: 99%
“…Recently, reviews have examined technology-based rehabilitation, both for cognitive deficits (Bogdanova et al, 2016 ; Sigmundsdottir et al, 2016 ) and language deficits (Lee and Cherney, 2016 ; Zheng et al, 2016 ) and have found preliminary evidence for the effectiveness of this method of rehabilitation. Importantly, the reviews highlight the need for more research due to vast differences in methodological designs, thereby, limiting the breadth of conclusions that can be drawn about the efficacy of such approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Another review 30 that focused specifically on computerised cognitive training (CCT) in ABI and on outcomes classified within the framework of the International Classification of Functioning, Disability and Health (ICF) 31 included 96 primary studies that evaluated CCT. The authors noted that only 15% of these studies represented 'level 1′ evidence (i.e.…”
Section: Literature Reviewsmentioning
confidence: 99%